Hyaluronan-mediated mononuclear leukocyte binding to gingival fibroblasts - Hagenfeld, Daniel; Mutters, Nico T.; Kim, Ti-Sun (Clinical oral investigations, 2017)
Objectives Binding of mononuclear leukocytes to hyaluronan cable structures is a well-known pathomechanism in several chronic inflammatory diseases, but has not yet described for chronic oral inflammations. The aim of this study was to evaluate if and how binding of mononuclear leukocytes to pathologic hyaluronan cable structures can be induced in human gingival fibroblasts.
Gesehen am 03.05.2018